KEBERMAKNAAN KEPEMIMPINAN TRANSFORMASIONAL DAN PEMANFAATAN TEKNOLOGI INFORMASI DALAM MENDUKUNG PENINGKATAN KINERJA PEGAWAI - Toma, Jefri; Sjahruddin, Herman; Heslina, Heslina; Hamidin, Muh Irwan Nur (Gapenas Publisher, 2024)
The demand to produce performance to each individual (employee) is based on the conformity between the realisation and the target that must be achieved by employees and formulated on the established performance indicators and organisational needs. This study investigates and analyses the effects of transformational leadership style and the use of Information technology on employee performance. The data collection used primary data through distributing questionnaires using all employees of the Human Resources Development Agency of South Sulawesi Province as a population, the sample was drawn using total sampling so that a sample size of 138 employees was obtained, but the results of distributing questionnaires showed that there were 11 defective questionnaires leaving 127 questionnaires. Data analysis was carried out using structural equation analysis with the assistance of Partial Least Square. The results of testing the outer model show that if the construct of transpormational leadership style in the ideal influence dimension, so it must be excluded from the research model. The test results show that all constructs used meet the outer model testing criteria. Hypothesis testing through inner models provides evidence that the transformational leadership style is in a good categorization as well as the construct of the use of information technology which shows high intensity so that it is proven to be able to improve employee performance towards higher. Keywords: Transformational leadership, employee performance, information technology utilisation